2007
DOI: 10.1016/j.febslet.2007.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Coxsackie and adenovirus receptor (CAR) with the cytoskeleton: Binding to actin

Abstract: The Coxsackie and adenovirus receptor (CAR) is a cell adhesion molecule that is highly expressed in the developing brain. CAR is enriched in growth cone particles (GCP) after subcellular fractionation. In GCP, we identified actin as an interaction partner of the cytoplasmic domain of CAR. In vivo, actin and CAR co-immunoprecipitate and co-localize. In vitro, the binding is direct, with a K d of $2.6 lM, and leads to actin bundling. We previously demonstrated that CAR interacts with microtubules. These data sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Moreover, it has been suggested that CAR may be involved in processes during reorganisation of the cytoskeleton and thereby impact cell migration and invasion. Hereby, binding of CAR to actin, as been shown previously, may pose a central phenomenon (Huang et al, 2007). However, a more detailed understanding of mechanisms underlying functions of CAR in cancer cell motility in general, and gastric cancer cell migration and invasion in particular is currently still missing.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been suggested that CAR may be involved in processes during reorganisation of the cytoskeleton and thereby impact cell migration and invasion. Hereby, binding of CAR to actin, as been shown previously, may pose a central phenomenon (Huang et al, 2007). However, a more detailed understanding of mechanisms underlying functions of CAR in cancer cell motility in general, and gastric cancer cell migration and invasion in particular is currently still missing.…”
Section: Discussionmentioning
confidence: 99%
“…How CAR is linked to the endocytic machinery and whether this plays other biological roles than pathogen binding remain to be characterized. The ICD of CAR contains numerous sequences that could be involved in protein-protein interaction and influence endocytosis (32,33). CAR could also regulate the trafficking of other proteins potentially important for CAV-2 entry, as described for E-cadherin (38) or acid sensing ion channel 3 (39).…”
Section: Discussionmentioning
confidence: 99%
“…28,29 CAR also interacts with actin and microtubules, leading to dynamic reorganization of the cytoskeleton. 13,14 Together, CAR might benefit the bladder uroepithelium under fluid shearing stress by participating in the anchoring junctions between the epithelial cells and basal lamina and by interaction with the cytoskeletons. The lack of an intracellular tail will result in the loss of targeting of CAR to the TJs, and differences in the tail ends between the 2 CAR isoforms (amino acid 340-365 in CAR-1; amino acid 340-352 in CAR-2) affects their subcellular localization.…”
Section: Commentmentioning
confidence: 99%
“…Furthermore, CAR interacts with actin and microtubules, leading to dynamic reorganization of the cytoskeleton. 13,14 The mouse CAR gene is composed of Ն8 exons, and CAR splice variants that differ at the end of the cytoplasmic tail have been identified in a number of tissues. 14,15 CAR can elicit a negative signal cascade to modulate the cell cycle regulators of bladder cancer cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation